Rekonstruksi Peran Nafkah Dalam Rumah Tangga: Analisis Fenomena Fatherless Menurut Pasal 80 Kompilasi Hukum Islam - Haniva Shafa Anjani; Linda Firdawaty; Idrus Alghiffary (Kartika: Jurnal Studi Keislaman, 2026)
The obligation of a husband to provide maintenance within the family is often understood narrowly as merely fulfilling material needs, thereby neglecting moral, emotional, and child-rearing dimensions. This limited understanding raises academic concern, as it may lead to the phenomenon of fatherlessness even when the father is physically present in the family. This study aims to analyze the husband’s maintenance obligations from the Islamic perspective, the provisions of Article 80 of the Compilation of Islamic Law, and Law Number 1 of 1974, as well as their relevance to the emergence of fatherless conditions. The research employs a normative juridical method using legislative and conceptual approaches. The findings indicate that maintenance in Islam encompasses not only economic support but also obligations of protection, religious guidance, and fulfillment of the psychological needs of both wife and children. The husband is positioned as the primary party responsible for family welfare in both material and non-material aspects. Neglect of these responsibilities contributes to fatherlessness, which is caused not only by biological absence but also by weak paternal caregiving and leadership roles. This condition negatively affects children’s emotional development and family stability, highlighting the importance of a comprehensive understanding of maintenance obligations to strengthen family resilience.